Failure analysis and prediction for DCD relay in the application of power system - Wong, Kenneth Hui Zhong (Nanyang Technological University, 2021)
A new field of engineering studies on the relay application in the power system reveals that failure of relay would give a huge disturbance to the power system and it may even lead to an outage in the network. To determine when the failures occur and how can we prevent those failures, a few models had been conducted out by the researchers. The model includes the simulation of the power flow for fast dynamics and slow dynamics, this simulates the power grid growth because relay failure causes the majority disturbance in the power system. Through the testing, the larger the amount of data collected from the sample, the more accurate the model will be, was determined. It was concluded that each individual’s instability of the devices will create a higher chance of disturbance in the network. Hence, the maintenance needed to be done before the failure occurs, so as to reduce the probability of major disturbance in the power system. These set a new question of how to prevent all this occurrence from occurring, and an experiment needed to be conducted.